Analysis of distressed reinforced concentrate bridges - Thanoon, Waleed Abdulmalik; Jaafar, Mohd Saleh; Chong, Kau Ping; Trikha, D. N. (2001)
The structural response of reinforced concrete bridges subjected to loss of concrete under JKR-SV (Jabatan Kerja Raya - Special Vehicle) loading is presented. The study focuses on the effect of concrete cracking, spalling and bad concreting on the structural behaviour and performance of a reinforced concrete beam girder bridge. The effects of the location. length and depth of the concrete loss, amount of tension steel on the structural performance of the distressed reinforced concrete bridges have been considered. Non-linear analysis using finite element method (FEM) has been used to trace the behaviour of reinforced concrete bridges in terms of deflection, strain and stress distribution and yield load.